Improving kidney transplantation through the addition of pharmacological agents to hypothermic preservation solutions: a scoping review - Mayoral, Vincent; Darius, Tom; Bruneau, Sarah; Masset, Christophe; Rigaud, Jérôme; Blancho, Gilles; Prudhomme, Thomas; Branchereau, Julien; Mesnard, Benoît (Frontiers in Pharmacology, 2026)
The increasing use of extended kidney grafts to bridge organ shortage has led to delayed and impaired graft function, warranting the development of new preservation strategies. In addition to hypothermic machine perfusion, the addition of pharmacological agents to preservation solutions has been primarily investigated, with a few promising agents making their way into clinical trials. This review aimed to identify and summarize current literature studies on pharmacological treatment additives for hypothermic kidney graft preservation. A scoping review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines. A comprehensive literature search was performed using Medline and Cochrane Library databases until 1 December 2023. All studies published in English reporting on pharmacological supplementation of preservation solutions to improve hypothermic kidney graft preservation were included. A total of 67 records were retrieved, all of which were preclinical except one. Of these, 8 were conducted on cellular models, 21 on ex vivo kidneys, and 38 on animal kidney transplantations. A total of 40 pharmacological agents were evaluated based on the key markers of ischemia–reperfusion injury (IRI) pathophysiology, most of them showing promise in kidney preservation. Although promising, with numerous preclinical studies identifying various effective additives, the pharmacological treatment additive strategy to improve hypothermic kidney preservation has still not been translated into clinical practice. Clinical investigations should be promoted to support few ongoing trials offering encouraging outcomes.